DAMPAK SOSIAL EKONOMI MASYARAKAT TERHADAP KESEJAHTERAAN PETANI JAGUNG REBUS DI KELURAHAN KAISABU BARU KECAMATAN SORAWOLIO - Agustina Syarifudin; Andy Arya Maulana Wijaya; Anwar Sadat (Governance, 2024)
Corn is a one of horticultural commodity in Kota Baubau, that is widely cultivated by producers in various farming businesses. To increase sweet corn production according to consumer demand, farmers use empty land to plant sweet corn in order to meet consumer demand. The people of Kaisabu Baru, apart from being farmers, are also direct sellers of boiled corn from their harvest in order to increase farmers' income to meet their social and economic needs. The size of the farmer's income greatly influences the farmer's own motivation in carrying out his farming business. The aims of this research are 1) to find out the social and economic impact of the boiled corn farming community in Kaisabu Baru Village, Sorawolio District. 2) To find out what the level of welfare of the boiled corn farming community is in Kaisabu Baru Village, Sorawolio District. The sampling method in this research is the purposive sampling method. Data processing and analysis uses one method, namely descriptive qualitative. The results of the research show that 1) the socio-economic impact felt by boiled corn farmers has provided positive changes. 2) the level of welfare of the boiled corn farming community in Kaisabu Baru Village has increased